PENGGUNAAN MEDIA GAMBAR DALAM PENINGKATAN KUALITAS HASIL BELAJAR SISWA DI TADIKA AL FIKH ORCHARD BANDAR PARKLAND SELANGOR MALAYSIA: The Use of Image Media in Improving the Quality of Student Learning Outcomes at Tadika Al Fikh Orchard Bandar Parkland Selangor Malaysia - Rani Lestari; Hasrian Rudi Setiawan (TA'LIMUNA: Jurnal Pendidikan Islam, 2025)
This study aims to explore the use of image media in improving the quality of student learning outcomes at Tadika Al Fikh Orchard Bandar Parkland Selangor Malaysia. In the context of education, image media is expected to increase students' interest and understanding of the material being taught. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the use of image media can strengthen the attractiveness of learning, increase student engagement, and facilitate understanding of basic concepts. In addition, the interaction between teachers and students also increases, creating a more dynamic learning atmosphere. Thus, this study concludes that image media is an effective tool in improving the quality of student learning outcomes at Al Fikh Kindergarten, as well as providing recommendations for wider application in the learning process in educational institutions.  Penelitian ini bertujuan mengeksplorasi penggunaan media gambar dalam peningkatan kualitas hasil belajar siswa di Tadika Al Fikh Orchard Bandar Parkland Selangor Malaysia. Dalam konteks pendidikan, media gambar dapat meningkatkan minat dan pemahaman siswa terhadap materi yang diajarkan. Metode yang digunakan dalam artikel ini adalah pendekatan kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penggunaan media gambar dapat memperkuat daya tarik pembelajaran, meningkatkan keterlibatan siswa, serta memfasilitasi pemahaman konsep-konsep dasar. Selain itu, interaksi antara pengajar dan siswa meningkat dan menciptakan suasana belajar yang lebih dinamis. Dengan demikian, artikel ini menyimpulkan bahwa media gambar merupakan alat yang efektif dalam meningkatkan kualitas hasil belajar siswa di Tadika Al Fikh, serta memberikan rekomendasi untuk penerapan yang lebih luas dalam proses pembelajaran di lembaga pendidikan. Kata Kunci : Hasil belajar; Media Gambar; Tadika.